커넥티드 차량 엔디엔 네트워크 안에 푸쉬 기반 정보 서비스를 위한 전달 기법 분석 - 임헌국(Huhnkuk Lim) (한국정보통신학회논문지, 2021)
When VNDN technology is used as a communication technology for infotainment application services of connected vehicles, it is possible to realize data-centric networking technology in which data is the subject of communication.Vehicle security attacks and hacks, performance degradation during long-distance data transmission, and frequent data loss It is possible to innovate the limitations of the current host-oriented Internet-based infotainment application service technology of connected vehicles. The data packet forwarding issue to deliver critical information data that is very sensitive to delay in the VNDN on a push-based basis to RSU (Road Side Unit), etc. is one of the issues to be solved for realizing VNDN-based application services. We comprehensively analyze existing forwarding techniques to support push-based data traffic under the environment, and compare and analyze each technique in terms of performance. VNDN 기술을 커넥티드 차량의 인포테인먼트 응용 서비스를 위한 통신 기술로 활용할 시 데이터가 통신의 주체가 되는 데이터중심네트워킹 기술 실현이 가능하며, 차량 보안 공격 및 해킹, 장거리 데이터 전송 시 성능 저하, 잦은 데이터 끊김 현상 등 현재의 호스트 중심 인터넷에 기반한 커넥티드 차량의 인포테인먼트 응용 서비스 기술이 갖는 한계를 극복 할 수 있다. VNDN 안에 지연에 매우 민감한 critical 정보 데이터를 RSU(Road Side Unit) 등에게 푸쉬 기반으로 전달해 주기 위한 Data 패킷 포워딩 이슈는 VNDN 기반 응용 서비스 실현을 위해 해결해야 할 이슈 중 하나이며, 이를 해결하기 위해 먼저 NDN 환경하에서 푸쉬 기반 데이터 트래픽을 지원해주기 위한 현존하는 포워딩 기법들을 포괄적으로 분석해 보고 각 기법 들을 성능 측면에서 비교 분석해 본다. 이를 통해 VNDN 환경하에서 보다 향상된 푸쉬 기반 중요 데이터 포워딩 기법 연구를 위한 사전 지식으로 활용되어질 수 있기를 기대한다.